La polémica Verón, Sebreli, Masotta y la problematización de la literatura como objeto crítico - Tuset Mayoral, Vicenç (Romanica Silesiana)
The controversy among Juan José Sebreli, Eliseo Verón and Oscar Masotta represents a very significant episode in the encounter between Marxist and Structuralist paradigms in Argentinian intellectual history. The main goal of the following paper is to show how the debate between the two programs had resulted in a loss of centrality of literature in the cultural debates that were held on the contemporary intellectual field. In addition, it shows how that process of de-centration affects the reconceptualization suffered by other categories, such as the concept of alienation and the notion of everyday life. Key words: Structuralism, Marxism, Literary Criticism, Alienation, Everyday Life.